South-south cooperation in the era of global value chains: What can China offer? - Shunli Yao (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2018)
China is a success story of inclusive trade growth as a result of its participation in Global Value Chains (GVCs). It is in transition from a processing and assembly hub towards an innovation centre, and is becoming a regional supplier of research and development (R&D) intensive parts and components. The infrastructure projects under the Belt and Road Initiative (BRI), a quasi-regional trade arrangement, are helping to improve regional connectivity and production linkage, but Chinese manufacturing also bring shocks to local production and employment. To achieve the full potential for job creation through production linkage with China as well as to buffer the shocks, BRI countries may consider a special customs regime to help build labour-intensive assembly and processing manufacturing. China's processing trade regime is an innovation in this regard and could be part of the strategy of inclusive trade growth for other developing countries. Inclusive trade is becoming a policy imperative, not only because governments in BRI countries need popular support for their foreign trade and investment policies, but also because it is in China's interest to establish mutually beneficial GVCs in order to help lay the political economy foundation for BRI and other initiatives.
Keywords: F15; O19; F50; 330; Global Value Chains; South-South cooperation; China